Interactions in e-learning in undergraduate courses - Fahad N. Alfahad, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The purpose of this paper is to investigate the common characteristics of the use of interaction (UI) from cases in Saudi Arabia. This study investigates the interactions between students, instructors, interface, and the content in distance education courses. The study was conducted in the College of Applied Studies and Community Service at King Saud University. The survey was distributed to 505 female college students selected randomly from a pool of 1,500 female students who were attending five basic courses in different areas. The measurements of interaction included frequency and interval. An exploratory factor analysis was used to examine the common components in this context. The result revealed that UI is composed of three main factors, namely human-to-human interactions, human-to-non-human interactions, and access duration. The results of this study show the use of interactions, which reflects the students’ actual use. This study also helps give administrators and instructors a better understanding of the pattern of interaction from the student perspective. It could be implied that students perceived the interaction in three distinct contexts by means of out-of-class communication, channel to learning experiences, and time spent